Imaging of the postoperative spine - Kaur, Simranjeet; Lalam, Radhesh; Trivedi, Rishi (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
There has been a significant increase in the number of spinal surgical procedures performed over the last few decades, resulting in a proportionate increase in the number of postoperative imaging studies.An exhaustive literature search was performed along with consideration of various guidelines and expert opinions regarding postoperative spine imaging. Complications are divided into early (in the first few weeks) and delayed, depending on the time of onset. Some complications occurring in the early postoperative period are common for both the instrumented and non-instrumented spine. Delayed complications are specific to the type of surgery performed and have been described as such. This review discusses the normal postoperative appearance and the various early and delayed complications.An understanding of the normal postoperative appearance is pertinent to distinguish normal from abnormal. A plain radiograph is the primary imaging modality for immediate postoperative assessment and long-term follow-up after spinal instrumentation. MRI with or without contrast is the imaging modality of choice for the evaluation of the postoperative spine. CT is the best modality for the assessment of the instrumented spine and status of bony fusion. Imaging assessment of the postoperative spine is complex and requires knowledge of key factors for interpretation like indications for the initial surgical procedure, type and approach of the surgical procedure, instrumentation used, time elapsed since surgery, and clinical complaints.
Keywords: spine; metalwork; decompression; discectomy; fusion; postoperative